Hukum Perubahan Status Harta Benda Wakaf: Studi Kasus Perubahan Status Kepemilikan Tanah Wakaf di Desa Keniten Kecamatan Kedungbanteng Kabupaten Banyumas - Sarmo, Sarmo (Fakultas Syariah IAIN Purwokerto, 2020)
This article discusses the practice of changing waqf for socio-educational purposes. The jurists of the fiqh schools argue over the permissibility of exchanging waqf land. As a country where the majority of the population is Muslim, Indonesia has made the guidelines for waqf which are stated in the law. No. 41 of 2004 concerning Waqf, Government Regulation Number 42 of 2006 concerning the implementation of law number 41 of 2004, and the Compilation of Islamic Law in Indonesia. This study is field research conducted in Keniten Village, Kedungbanteng District, Banyumas Regency. This study concluded that the exchange of waqf land in this village was in accordance with the purpose of the waqf and in accordance with the law. No. 41 of 2004 Article 41 paragraph (3). The process of changing donated land for TK Diponegoro 136 is in accordance with Government Regulation Number 42 of 2006 concerning the implementation of law number 41 of 2004. Meanwhile, the relation of Islamic law to the exchange of waqf land in Keniten Village, Kedungbanteng District, Banyumas Regency is debated in accordance with the rules used by each jurisprudence school. Referring to the argument of jalb al-maá¹£Äliá¸¥ wa dar 'al-mafÄsid, the exchange of waqf land in Keniten Village, Kedungbanteng District, Banyumas Regency is not against Islamic law because it brings more benefits.